Rehabilitation of orthopaedic and neurologic boxing injuries - Lefkowitz, T.; Flanagan, S.; Varlotta, G. (Clinics in Sports Medicine, 2009)
Clinical decision making for injured boxers follows the same therapeutic principles as the treatment plan for other injured athletes. Just as surgical techniques have improved, so has the scientific basis for implementing therapeutic exercises progressed to return the athletes to their former level of competition.